REPLACEMENT OF LAND ACQUISITION FIR DEVELOPMENT FOR THE PUBLIC INTEREST OF THE BALIKPAPAN - SAMARINDA TOLL ROAD BASED ON LAW 2 OF 2012 - Revaldy, Muhammad Arsy; Lana, Aminah (Jurnal Meta-Yuridis, 2025)
in regard to the objection to the incompatibility of compensation for land acquisition managers in East Kalimantan Province, The inconsistency of the compensation given with the area of land used, the area of land that has been given compensation is only 842 m2 while the land used in land acquisition is 5428 m2. The formulation of the problem in this study is: Whether the appropriateness of the provision of compensation for control is in accordance with the Implementation Stage of Land Acquisition based on Law Number 2 of 2012 and whether the decision of the Samarinda District Court Number 28/Pdt.G/2018/PN Smr is in accordance with Law Number 2 of 2012 concerning Land Acquisition for Development for the Public Interest. Research Methods Using descriptive research that is normative, the collection of data for this research is based on secondary data carried out with the help of literature research, data analyzed by qualitative methods with deductive logic. The result of the research and discussion is that the value of compensation given by the land acquisition implementer is not in accordance with the principle of justice. The conclusion of the study is that the compensation given by the implementer is not in accordance with the principles of land acquisition. The judge's decision in accordance with Law No. 2 of 2012 regarding the submission of objections is carried out within 14 days after the value of compensation is determined in the deliberations.